Monocyte Expression Levels of Cytokines in Patients With Fibromyalgia Syndrome - Evrim ÖĞÜT; Ali GÜR; Burhan Fatih KOÇYİĞİT and Serdar ÖZTUZCU and Beyhan CENGİZ and Özlem ALTINDAĞ and Hilal KARAGÜLLÜ and Savaş GÜRSOY (Archives of Rheumatology, 2015)
Objectives: This study aims to determine monocyte expression levels of interleukin 1 beta (IL-1β), IL-6, IL-8, and tumor necrosis factor alpha in fibromyalgia syndrome (FMS) patients and healthy females. Patients and methods: A total of 80 female FMS patients and 50 healthy females were evaluated. Twelve of the FMS patients who did not meet the 1990 American College of Rheumatology criteria and 10 healthy controls were excluded. After exclusion 68 participants as FMS patient (mean age 41.41±7.14 years; range 18 to 55 years) and 40 participants as control group (mean age 39.12±10.9 years; range 18 to 55 years) were included in the study. For both groups, a detailed form was filled out which included information on age, body mass index, marital status, educational status, visual analog scale, fibromyalgia impact questionnaire, Hamilton anxiety scale, Hamilton depression scale, modified fatigue impact scale, and Nottingham health profile. Whole blood peripheral blood monocyte cells were drawn in ethylenediaminetetraacetic acid tubes from patient and control groups between 08:30 to 9:30 hours. Tumor necrosis factor alpha, IL-6, IL-8, and IL-1β expressions were evaluated using fluorescence-activated cell sorting flow cytometry device. Results: No statistically significant difference was detected between the two groups in terms of average age, body mass index, and other demographic data (p>0.05). Visual analog scale, Hamilton anxiety scale, Hamilton Depression Scale, fibromyalgia impact questionnaire, modified fatigue impact scale total score and Nottingham health profile total-subscore values were statistically significantly higher in the patient group than the control group (p<0.001). No significant difference was found in expression of cytokines by monocytes in patients with FMS (p>0.05). Conclusion: Although FMS is not traditionally considered an inflammatory disorder, evidence for elevated inflammatory processes has been noted in some studies. Our results do not support any role of the inflammatory cytokines in the pathogenesis of FMS.